Developing professional ethical care through co-creation in ECEC in Norway: A qualitative study - Anne Synnøve Brenne; Ingvild Amot (Journal of Childhood, Education & Society)
The article analogizes findings from the project Children in Central Norway, Mental Health in ECEC. A preventive factor for children’s mental health in early childhood education and care (ECEC) is the sensitive relationship between children and staff. ECEC staff in three municipalities participated in a competence-raising package for children’s mental health. Subsequently, 33 members of staff attended five focus-group interviews. Research question: In what way have ECEC staff’s experience changes in their relationship with the children after working with the competence-raising package for mental health, and what kind of processes appeared during this work? The qualitative data has been analyzed using reflexive thematic analysis, while the discussion is rooted in ethics of care and based on children’s rights. The findings show that the staff describe the development of compassionate pedagogy and a common language for children’s needs for attachment. This facilitates a collective professional language through co-creating processes and affects the relational quality in ECEC.